Is ABO-Incompatible Living Donor Liver Transplantation Really a Good Alternative for Pediatric Recipients? - de Magnée, Catherine (Children (Basel), 2021)
Background: ABO-incompatible (ABOi) living donor liver transplantation (LDLT) has been proposed to compensate for donor shortage. To date, few studies have reported detailed ABOi LDLT results in large series of pediatric patients. C4d complement deposition in graft capillaries has been reported to be associated with antibody-mediated rejection in solid organ transplantation. Methods: A retrospective case–control study was conducted, comparing clinical outcomes of each of 34 consecutive pediatric ABOi LDLT recipients with those of 2 non-ABOi pairs (n = 68), matched according to pre-transplant diagnostic criteria, age, and date of transplantation. In addition, we studied the C4d immunostaining pattern in 22 ABOi and in 36 non-ABOi recipients whose liver biopsy was performed within the first 4 post-transplant weeks for suspected acute rejection. Results: The incidence of biliary complications was higher in ABOi recipients (p < 0.05), as were the incidence of acute humoral rejection (p < 0.01) and the incidence of retransplantation (p < 0.05). All children who required retransplantation were older than 1 year at the time of ABOi LDLT. Positive C4d immunostaining was observed in 13/22 (59%) ABOi recipients versus 3/36 (8.3%) non-ABOi recipients (p < 0.0001). Conclusions: ABOi LDLT is a feasible option for pediatric end-stage liver disease but carries increased risks for the recipient, especially for children older than 1 year, even with a specific preparation protocol. C4d immunostaining may be a hallmark of acute humoral rejection in ABOi liver transplantation.